Lets start from the beginning.
We need to use this property, which by chance I had told you in the earlier post. \(\sf\Large a(b+c)=ab+ac\)
HOWEVER, your question is \(\sf\Large -3(b-7)\)
so since you have a problem with negative numbers, let me make it a little easier on you :)
\(\sf\Large -a(b-c) = -ab + ac\) Remember to carefully look at the - and +'s :)
Okay. Still don't really get it.
just replace the a with 3 and the c with 7
-3(7) = -21?
Is this right?
\(\sf\Large-3(b – 7)=\\\sf\Large (-3)(b) - (-3)(7)=? \)
and that is correct :)
So i do need to do anything else with this problem?
but 21 isn't the final answer.
so far you have gotten: \(\sf\Large (-3)(b) - (-3)(7)=-3b-(-21)\)
Why is it saying i'm typing and half the time i'm not. XD
So do i solve for b?
that's an OpenStudy glitch xD
and no, just simplify that what is - (-21) = ?
so your final answer would become: \(\sf\Large -3b+21\)
Alright thank you so much ^ ^
Openstudy not letting me close the question